2019
DOI: 10.1155/2019/6309465
|View full text |Cite
|
Sign up to set email alerts
|

Redox Balance Correlates with Nutritional Status among Patients with End-Stage Renal Disease Treated with Maintenance Hemodialysis

Abstract: Over 50% of end-stage renal disease (ESRD) patients die of cardiovascular disease. ESRD patients treated with maintenance hemodialysis are repeatedly exposed to oxidative stress. The aim of the study was to find the relationship between lifestyle factors, nutritional status, calcium-phosphate metabolism, and selected redox parameters such as glutathione peroxidase (GPx), glutathione reductase (GR), superoxide dismutase (SOD), uric acid (UA), and total antioxidant capacity expressed as ferric reducing antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Possible explanation could be change in food intake. Those patients who consumed more fruits and vegetables had a higher uric acid level which could be attributed to an overall higher intake of food and high-purine products (67). Uric acid is a powerful oxygen radical scavenger in hydrophilic environments, and a study on a large cohort showed that low and not high serum uric acid level predicted all-cause and CV mortality (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanation could be change in food intake. Those patients who consumed more fruits and vegetables had a higher uric acid level which could be attributed to an overall higher intake of food and high-purine products (67). Uric acid is a powerful oxygen radical scavenger in hydrophilic environments, and a study on a large cohort showed that low and not high serum uric acid level predicted all-cause and CV mortality (68).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the risk of elevated potassium and uid overload may lie behind decreased fruit and vegetable consumption in this group of patients (74). Malnutrition and hypoalbuminemia reduce antioxidant defence (75) and albumin and prealbumin, commonly used nutritional markers, possess antioxidant properties and can account for signi cantly lower FRAP values in HD patients when compared with the healthy controls (67). Despite signi cant seasonal variation in serum albumin, prealbumin and uric acid level our results did not show seasonal variations in FRAP and vitamin C. These ndings suggest that many other components contribute to total antioxidants capacity of plasma in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that dietary antioxidants can protect the body against oxidative damage and reduce the risks of some clinical complications [20,35,36]. Sahni [37] compared the nutritional status of healthy subjects and CKD patients and observed that individuals with the poorest nutritional status had the lowest dietary antioxidant intake. In addition, intake was found to be directly proportional to antioxidant capacity [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to highlight that oxidative-inflammatory stress is increased even in the early stages of CKD and progresses in parallel to the deterioration of renal functions [5,12,14,15]. Moreover, the presence of other non-conventional risk factors, such as anemia [17,18], or several lifestyle factors, such as nutrition or dietary interventions [6,19], also have a great impact on the redox status of CKD patients, promoting oxidative-inflammatory stress, and consequently, aggravating progression to renal failure and CVDs in these patients [6,[17][18][19]. In fact, advanced CKD patients may suffer from malnutrition or dietary restrictions, which, together with the loss of micronutrients during dialysis procedures, may further increase oxidative stress due to the reduction of extracellular antioxidant defenses [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an inadequate intake of oligoelements (e.g., copper, manganese, etc.) may draw on misleading antioxidant enzymes [19]. However, medical nutrition therapy (e.g., low-protein diet restriction) may be useful in decreasing uremic toxicity and increasing the efficiency of muscle and body metabolism in severe CKD patients [20].…”
Section: Introductionmentioning
confidence: 99%